Prison architecture, design and technology 2014-2017 - Jewkes, Yvonne (UK Data Service, 2019)
This international, interdisciplinary project provides new perspectives on the experience of prison for a range of end users. Using innovative mixed methods its aim is to critically analyze current developments in penal architecture, the design of carceral spaces and the impact of advanced technologies of communication, surveillance and monitoring of movement, with a view to providing a theoretically informed, empirically grounded and comparative account of prison architecture, design and technology (ADT) and their effects on prisoners, staff and prison visitors. Tracing the commission, design and construction of two UK prisons, the project explores: (i) the intentions behind the architecture, design and technologies of spatial management and control that characterize the recent penal estate, paying attention to external and internal spaces, and incorporating consideration of the introduction of Building Information Modelling (BIM) to the UK custodial sector; (ii) the impacts of the architecture, design and technologies of spatial management and control that characterize both the recent UK and northwest European penal estate. This research investigates developments in the design of prisons, exploring the propositions that punishment is manifested architecturally, that 'good' prison design need not cost any more than 'bad' design, that architecture, design and technology (ADT) may impact on prisoners' emotional and psychological reactions to incarceration, including their behaviour, their willingness to engage with regimes and their capacity to build positive relations with other prisoners and staff, and that ADT may significantly influence prisoners' prospects of rehabilitation and reintegration into society on release. One 'lifer' notes that many of the crises facing penal systems in the developed world (including overcrowding, violence, mental and physical illness, drug use, high levels of suicide, self-harm etc.) are intrinsically related to the 'fear-suffused environments' created by prison architects (Hassine, 2008: 8). This research critically interrogates this statement. Against that backdrop, a few new penal experiments in parts of northern and western Europe might be welcomed as 'humane' alternatives to the traditional architecture of incarceration. Equipped with state-of-the-art lighting imitating natural daylight, extensive use of glass, no bars on windows, different colour palettes creating varied atmospheres in each 'zone', displays of artwork, curved lines, rounded walls and uneven horizons, the design features being incorporated into some new prisons might be assumed to mitigate against the harms caused by imprisonment. But can aesthetic considerations make a difference to behaviour? If, as 19th century prison commissioners and designers believed, architecture can be used as a means of inflicting punishment, is it equally true that architecture can deliver rehabilitation? Should the briefs issued to those who design and plan new prisons include a requirement to build into their construction features that normalize carceral space and have potential to ease offenders' reintegration back into society? Or is it simply that 'a prison is a prison', regardless of the enlightened humanism that may underpin its design? Could it even be that these prisons have unintended outcomes and perverse consequences, or represent an extension of power and control orientated towards docile compliance and bring their own distinctive pains of imprisonment? Moreover, if the general public are as punitive in their attitudes to offenders, as is commonly thought, how do communities feel when prisons are built in their midst? How do architects of prisons balance the requirements that prisons should pass the 'public acceptability' test (which may include an expectation that they should 'look' and 'feel' like places of punishment) with the 'NIMBYism' which frequently greets the announcement of a new prison? This project will empirically investigate these issues and inform future debates about how prisons might be designed differently in order to fulfill the goal of rehabilitation as well as those of security, deterrence, retribution and punishment. Challenging conventional wisdom and taken-for-granted assumptions concerning the purposes and 'effectiveness' of prisons, the proposed project is innovative, significant and timely. No research currently exists on the impact and effects - on prison staff as well as on inmates - of penal architecture, spatial design and the implementation of advanced monitoring, surveillance and communication technologies. The study's intent is to move beyond the traditional, historical focus on penal architecture e.g. the legacy of Bentham's Panopticon and the 19th century 'separate' and 'silent' systems (in which the goals of discipline and reform were built in to the fabric of the carceral environment), and to inform knowledge and debates from a contemporary and future-oriented perspective. In doing this, the proposed project promises to deliver significant advances on previous research and extant knowledge.